The Effect of Company Size, Financial Leverage, Profitability, and Dividend Payout Ratio on Income Smoothing Practices - Sintia Dewi; Bayu Pratama (Journal of Accounting, Management, and Economics Research (JAMER), 2023)
This study aims to test whether company size, financial leverage, profitability, and dividend payout ratio affect earnings smoothing practices in LQ-45 index companies on the Indonesia Stock Exchange in 2018-2020. This research uses quantitative methods. The population in this study is the LQ-45 company index with a sample recruitment technique using purposive sampling. The selected samples were 19 companies through predetermined sample criteria. Hypothesis testing uses logistic regression analysis, and data is processed using E-Views 10 software. The results of this study indicate that company size has a significant positive effect on the practice of the role of profit, financial leverage has a significant and negative effect on the practice of the role of profit, profitability has an effect and is significant positive effect on income smoothing practices, dividend payout ratio has no effect on income smoothing practices in LQ 45 index companies on the Indonesia Stock Exchange in 2018-2020.